2021
DOI: 10.1101/2021.03.26.437051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histologic and Proteomic Remodeling of the Pulmonary Veins and Arteries in a Porcine Model of Chronic Pulmonary Venous Hypertension

Abstract: AIM: In heart failure (HF), pulmonary venous hypertension (PVH) produces pulmonary hypertension (PH) with remodeling of pulmonary veins (PV) and arteries (PA). In a porcine PVH model, we performed proteomic-based bioinformatics to investigate unique pathophysiologic mechanisms mediating PA and PV remodeling. METHODS: Large PV were banded (PVH, n= 10) or not (Sham, n=9) in piglets. At sacrifice, PV and PA were perfusion labeled for vessel specific histology and proteomics. The PA and PV were separately sampled … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…3,22 Our study adds to the growing list of available models that approximate features of pathological pulmonary vascular remodeling in HFpEF. [23][24][25] The L-NAME/ HFD model has several distinct advantages in that it is technically straightforward to implement, replicates known deficits in nitric oxide (NO) and protein kinase G (PKG) signaling from human studies of HFpEF, 26,27 recapitulates many extracardiac features of HFpEF, including metabolic disease that is prominent in the human condition, 28 and is amenable to further mechanistic studies. Using a discovery-based approach, our study found inflammatory pathways to be altered in the remodeling lung of PH-HFpEF mice.…”
Section: Discussionmentioning
confidence: 99%
“…3,22 Our study adds to the growing list of available models that approximate features of pathological pulmonary vascular remodeling in HFpEF. [23][24][25] The L-NAME/ HFD model has several distinct advantages in that it is technically straightforward to implement, replicates known deficits in nitric oxide (NO) and protein kinase G (PKG) signaling from human studies of HFpEF, 26,27 recapitulates many extracardiac features of HFpEF, including metabolic disease that is prominent in the human condition, 28 and is amenable to further mechanistic studies. Using a discovery-based approach, our study found inflammatory pathways to be altered in the remodeling lung of PH-HFpEF mice.…”
Section: Discussionmentioning
confidence: 99%